PERLINDUNGAN HUKUM TERHADAP ALIRAN MENYIMPANG DI INDONESIA - M. Iwan Satriawan (Universitas Lampung, 2015)
During Soeharto’s adminitration which was called Orde Baru (New Orde) only five religions were admited by the government, they are Islam, Kristen Protestan, Kristen katolik, Hindu and Budha. But, since the era of the reformation in 1998, much faith has came up and developed in Indonesia, they are called “deviant” (aliran menyimpang). The existence of deviant in Indonesia, more due to different interpretations of the verses of the holy. It was also because the readings from different sources exegesis-commentaries. Efforts legal protection that has been done by the government in terms of addressing the emergence of deviant in Indonesia use two methods: by means of preventive and repressive.Keywords : Five Faith, Deviant.